Efficient Access to 3,5-Disubstituted 7-(Trifluoromethyl)pyrazolo[1,5-a]pyrimidines Involving SNAr and Suzuki Cross-Coupling Reactions - Badr Jismy; Abdellatif Tikad; Mohamed Akssira; Gérald Guillaumet; Mohamed Abarbri (Molecules, 2020)
An efficient and original synthesis of various 3,5-disubstituted 7-(trifluoromethyl)pyrazolo[1,5-a]pyrimidines is reported. A library of compounds diversely substituted in C-3 and C-5 positions was easily prepared from a common starting material, 3-bromo-7-(trifluoromethyl)pyrazolo[1,5-a]pyrimidin-5-one. In C-5 position, a SNAr type reaction was achieved by first activating the C–O bond of the lactam function with PyBroP (Bromotripyrrolidinophosphonium hexafluorophosphate), followed by the addition of amine or thiol giving monosubstituted derivatives, whereas in C-3 position, arylation was performed via Suzuki–Miyaura cross-coupling using the commercially available aromatic and heteroaromatic boronic acids. Moreover, trifluoromethylated analogues of potent Pim1 kinase inhibitors were designed following our concise synthetic methodology.